A Universal Polyiodide Regulation Using Quaternization Engineering toward High Value‐Added and Ultra‐Stable Zinc‐Iodine Batteries. Issue 13 (6th March 2022) - Zhang, Leiqian; Zhang, Mingjie; Guo, Hele; Tian, Zhihong; Ge, Lingfeng; He, Guanjie; Huang, Jiajia; Wang, Jingtao; Liu, Tianxi; Parkin, Ivan P.; Lai, Feili
Abstract: The development of aqueous rechargeable zinc‐iodine (Zn‐I2 ) batteries is still plagued by the polyiodide shuttle issue, which frequently causes batteries to have inadequate cycle lifetimes. In this study, quaternization engineering based on the concept of "electric double layer" is developed on a commercial acrylic fiber skeleton (1.55–1.7 kg −1 ) to precisely constrain the polyiodide and enhance the cycling durability of Zn‐I2 batteries. Consequently, a high‐rate (1 C–146.1 mAh g −1, 10 C–133.8 mAh g −1 ) as well as, ultra‐stable (2000 cycles at 20 C with 97.24% capacity retention) polymer‐based Zn‐I2 battery is reported. These traits are derived from the strong electrostatic interaction generated by quaternization engineering, which significantly eliminates the polyiodide shuttle issue and simultaneously realizes peculiar solution‐based iodine chemistry (I − /I3 − ) in Zn‐I2 batteries. The quaternization strategy also presents high practicability, reliability, and extensibility in various complicated environments. In particular, cutting‐edge Zn‐I2 batteries based on the concept of derivative material (commercially available quaternized resin) demonstrate ≈100% capacity retention over 17 000 cycles at 20 C. This work provides a general and fresh insight into the design and development of large‐scale, low‐cost, and high‐performance zinc‐iodine batteries, as well as, other novel iodine storage systems. Abstract : Herein, a universal quaternization engineering by the "electric double layer" concept is developed on commercially available polymer skeleton to precisely constrain the polyiodide. The as‐developed zinc‐iodine (Zn‐I2 ) batteries significantly eliminate the polyiodide shuttle issue and simultaneously realize solution‐based iodine chemistry (I − /I3 − ). Consequently, cutting‐edge Zn‐I2 batteries show ≈100% capacity retention after 17 000 cycles.